Selection bias in social facilitation theory? Audience effects on elite biathletes' performance are gender-specific. (July 2021) - Heinrich, Amelie; Müller, Florian; Stoll, Oliver; Cañal-Bruland, Rouwen
Abstract: Social facilitation proves robust in conditioning tasks (e.g., running), yet in coordination tasks (e.g., rifle-shooting) some studies report performance deterioration. Recent Biathlon World Cup data offered the unique opportunity to test this task-specificity (conditioning = cross country skiing, coordination = rifle-shooting). Audience restrictions due to COVID-19 allowed to compare athletes' performance in the absence (2020) and presence (season 2018/2019) of an audience. Gender-specific regulations (e.g., course length) necessitated the inclusion of gender as additional factor. Results of 83 (sprint competition) and 34 (mass start competition) biathletes revealed that task-specific social facilitation is moderated by gender: In the presence of an audience male biathletes showed performance improvements in the conditioning task and performance deteriorations in the coordination task; female biathletes showed the reverse pattern. This gender dependency may have gone unnoticed in the past due to sample selection bias (<1/3 female), thereby questioning the generalizability of social facilitation theory. Highlights: Social facilitation effects in elite biathlon are task- and gender-specific Male biathletes improve their performance in conditioning task (skiing) but deteriorate in coordination task (shooting) in the presence of an audience; female athletes show the reverse pattern Sample selection bias in past research (<1/3 female) may explain the results, thereby questioning the generalizability of social facilitation theory